Contextual and Strategic Differences Among Mature Businesses in Four Dynamic Performance Situations - Zeithaml, Carl P.; Fry, Louis W. (Academy of Management Journal, 1984)
Recent empirical studies have presented evidence that contradicts the presumed trade-off between changes in market share and profitability. This research attempted to resolve these inconsistent findings and to examine the conditions under which simultaneous increases in market share and profitability are found Contextual and strategic differences were identified among businesses in four dynamic performance situations.